(untitled) (Research, Society and Development, 2024)
Introduction: The electronic cigarette is a nicotine delivery device that has gained popularity since its creation in 2003, both as a smoking cessation method and for recreational use. Its attractiveness, discretion, and variety of flavors spark curiosity, particularly among teenagers and young adults. Despite being prohibited, the marketing of these devices raises concerns, especially due to the lack of clear evidence regarding safety, quality, and effects. Objective: To elucidate the effects that the use of electronic cigarettes can have on users’ health. Methodology: This is an integrative review with a qualitative descriptive approach, with data collection conducted from March to October 2023, using the Scielo, PubMed, and LILACS databases. Descriptors in English and Portuguese were used, including "electronic cigarette," "nicotine," "effects," "health," excluding "oral," "dental," "pregnant," and "smoking cessation." Results: Initially, 2,227 articles were identified, and 24 studies were selected after the established criteria. Discussion: Although electronic cigarettes may seem harmless and less toxic than traditional cigarettes, most analyzed articles reported pathological organic modifications and a detrimental relationship in various body systems, particularly pulmonary and cardiovascular, along with other effects such as hemodynamic, immunologic, neoplastic, and toxicological. Conclusion: There is evidence that the use of electronic cigarettes harms health, although data on the subject are limited. Therefore, further studies are needed on the use of electronic cigarettes, focusing primarily on assessing long-term impact, safety, regulation, and public health.